(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. Dry eye disease is a multifactorial condition, which is characterized by impairment of tear film formation. Lacrimal glands metabolism plays a critical role in dry eye disease. Emotional stress may impair lacrimal glands function. Purpose. We aimed to study production of nitric oxide from constitutive and inducible NO-synthases, activity of arginases and oxidative stress markers in lacrimal glands of rats during modeling of water avoidance stress (WAS) and its correction by metformin and corvitin. Material and methods. We concluded our experiment on 36 adult male rats of Wistar line weighing 190-240 g. Animals were divided into 6 groups consisting from 6 animals each, namely: control group, WAS group, group of correction by metformin (200 mg/kg) and group of correction by corvitin (10 mg/kg) during WAS modeling. And two drug-control groups. Results. WAS leads to increased activity of inducible NO-synthase, superoxide dismutase, catalase and concentration of MDA by 1.59, 1.93, 1.97 and 1.28 times respectively. Metformin and corvitin decreased activity of inducible NO-synthase by 8.25 and 8.5 times respectively, concentration of MDA decreased by 1.35 and 1.26 times respectively. Activities of superoxide dismutase did not change after introduction of metformin and corvitin. Metformin decreased catalase activity by 1.47 and corvitin increased it by 1.55 times. Production of superoxide dropped during WAS by 1.59 times and was increased to level below or equal that of control animals with introduction of metformin and corvitin. Conclusion. Increased activity of inducible NO-synthase during WAS is a possible reason of tissue damage in lacrimal glands of rats. Introduction of metformin or corvitin during WAS are an effective means for correction of tissue damage in lacrimal glands of rats due to their ability to lower increased inducible NO-synthase activity.